Determinan kinerja tenaga kesehatan dalam penemuan kasus baru TB - Cindy Alya Putri; Rumita Ena Sari; Usi Lanita; Adila Solida (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Based on national data for 2024, the number of Tuberculosis (TB) cases in Indonesia remains quite high, with an estimated 1,092,000 TB cases and 23,858 TB deaths. Meanwhile, the number of new cases detected reached 856,420, with a treatment coverage (TC) of 78% and a Treatment Success Rate (TSR) of 88%. However, this coverage rate still falls short of the Ministry of Health's 2024 Strategic Plan target of 90%. Successful TB elimination depends heavily on two main pillars: complete treatment and new case detection, both active and passive. Purpose: To analyze the determinants of health worker performance in TB case detection. Method: This quantitative study used a cross-sectional design. The sample consisted of 65 health workers participating in TB case detection at Jambi City Community Health Centers (Puskesmas), drawn using total sampling, considering inclusion and exclusion criteria. Data collection used a questionnaire. Univariate, bivariate, and multivariate data analysis. Results: The relationship between Ability and Health Worker Performance in TB Case Finding obtained a p-value of 0.000, indicating a significant relationship. The relationship between Clarity and Health Worker Performance in TB Case Finding obtained a p-value of 0.000, indicating a significant relationship. The relationship between Help and Health Worker Performance in TB Case Finding obtained a p-value of 0.058, indicating no significant relationship. The relationship between Incentives and Health Worker Performance in TB Case Finding obtained a p-value of 0.012, indicating a significant relationship. The relationship between Evaluation and Health Worker Performance in TB Case Finding obtained a p-value of 0.001, indicating a significant relationship. The relationship between Environment and Health Worker Performance in TB Case Finding obtained a p-value of 0.003, indicating a significant relationship between the work environment and the variable of health worker performance in TB case finding. Conclusion: There is a relationship between ability, clarity, incentive, evaluation, validity, and environment with the performance of health workers in TB case detection, and there is no relationship between Help and health worker performance. The variable Ability is the most dominant factor. Keywords: Performance, TB, ACHIEVE